Quality of web-based information at the beginning of a global pandemic: a cross-sectional infodemiology study investigating preventive measures and self care methods of the coronavirus disease 2019 - Jenny Stern; Susanne Georgsson; Tommy Carlsson (BMC, 2021)
Abstract Background reducing the spread and impact epidemics and pandemics requires that members of the general population change their behaviors according to the recommendations, restrictions and laws provided by leading authorities. When a new epidemic or pandemic emerges, people are faced with the challenge of sorting through a great volume of varied information. Therefore, the dissemination of high-quality web-based information is essential during this time period. The overarching aim was to investigate the quality of web-based information about preventive measures and self care methods at the beginning of the COVID-19 pandemic. Methods in May 2020, consumer-oriented websites written in Swedish were identified via systematic searches in Google (n = 76). Websites were assessed with inductive content analysis, the JAMA benchmarks, the QUEST tool and the DISCERN instrument. Results seven categories and 33 subcategories were identified concerning preventive measures (md = 6.0 subcategories), with few specifying a method for washing hands (n = 4), when to sanitize the hands (n = 4), and a method for sanitizing the hands (n = 1). Eight categories and 30 subcategories were identified concerning self care methods (md = 3.0 subcategories), with few referring to the national number for telephone-based counseling (n = 20) and an online symptom assessment tool (n = 16). Overall, the median total quality scores were low (JAMA = 0/4, QUEST =13/28, DISCERN = 29/80). Conclusions at the beginning of the pandemic, substantial quality deficits of websites about COVID-19 may have counteracted the public recommendations for preventive measures. This illustrates a critical need for standardized and systematic routines on how to achieve dissemination of high-quality web-based information when new epidemics and pandemics emerge.